The feeding ecology of harbour porpoises (Phocoena phocoena) in Norwegian coastal communities: a combined approach using stable isotope and stomach content analyses - Saint-André, Camille (UiT Norges arktiske universitet, 2019)
The harbour porpoise is a key predator in Norwegian coastal communities, therefore studying its feeding ecology is important to understand its ecological role and may shed light on the dynamics of Norwegian coastal ecosystems. The diet of 134 harbour porpoises bycaught in Autumn 2016 (n = 61) and Spring 2017 (n = 73) in Norwegian coastal waters and fjords was investigated using both stable isotopes (δ15N and δ13C) and stomach contents. A total of 23 prey groups were identified in the stomachs, though most porpoises had consumed between 1 and 4 prey groups. Harbour porpoises mainly fed on gadoid fishes, and saithe (juvenile) was by far the most important prey species. Pelagic, lipid-rich prey species such as capelin and herring contributed much less to the diet. While lipid-rich prey species are thought to be essential for harbour porpoises, due to their high metabolic demands, this study highlights the importance of lean but more available prey in the diet. Harbour porpoises mainly fed on small prey species or on the juveniles of large-sized gadoids (e.g. saithe, cod). Both the stable isotope and stomach content analyses showed a significant ontogenetic shift, with differences in the isotopic and diet composition of calves compared to the more similar juveniles and adults. The stable isotopes may suggest a greater use of benthic or coastal resources, or a decreasing reliance on dietary lipids to synthesize muscle tissues with increasing body size. There was no significant difference in the isotopic and diet composition between male and female porpoises, suggesting both use similar habitats and prey resources. Although saithe was dominant in all sampling periods and areas, spatiotemporal variations in diet were observed and are likely related to seasonal and geographical changes in prey availability (i.e., prey spawning, seasonal migrations, species distribution). However, spatiotemporal variations in stable isotope composition cannot conclusively be linked to the diet, as knowledge on the isotopic baseline in ...